Congestion Charging - das Beispiel Londons. Ökonomische Grundlagen und Zwischenbilanz. - Eichinger, Andreas; Knorr, Andreas (Deutscher Verkehrs-Verlag, 2004)
Unter Congestion Charging bzw. Road Pricing versteht man "die Erhebung von Entgelten für die einzelne Benutzung bestimmter Straßenabschnitte". Eines der weltweit größten Systeme dieser Art wurde am 17. Februar 2003 in London eingeführt, um die staugeplagte Innenstadt (Central London) nachhaltig vom Individualverkehr zu entlasten. Der Beitrag stellt die ökonomischen Grundlagen des Congestion Charging im Allgemeinen sowie die wichtigsten Merkmale des Londoner Systems im Besonderen vor und zieht eine erste Zwischenbilanz der bisherigen verkehrswirtschaftlichen Effekte der Londoner Congestion Charge. difu

A basic economic principle states that every user of a resource should bear the full costs incurred by using that specific resource in order to warrant an efficient resource allocation. On February 17th 2003, one of the world's largest and most sophisticated congestion charging schemes was introduced in Central London. The aim of the scheme was to significantly reduce the probability of and social costs caused by road congestion within the 21 square kilometre charging area. This article characterises the London scheme with the economics of road pricing as the theoretical benchmark. Furthermore, it examines the effects congestion charging has had in London during the first six months of its operation. difu
Keywords: Individualverkehr; Straßenverkehr; Stadtverkehr; Innenstadt; Verkehrspolitik; Gebühr; Straßenbenutzungsgebühr; Maut; Gebührenerhebung